Hva kan arves? Om skyld, vold og seksualitet i to nordiske krigsminneromaner - Langås, Unni (Scandinavistica Vilnensis, 2023)
During the last two decades, an increasing focus on perpetrators has emerged in Scandinavian literature. This so called perpetrator fiction, with an explicit intention of understanding evil, has portrayed the Nazis and their henchmen in detail. These are frequently described in familial relationships, and their stories are told from a second or third generational point of view. Interestingly, the perpetrators are regularly depicted as perverse persons and their deviant sexuality as part of the problem. In this article, I discuss two Scandinavian novels with the family as a narrative structure and the perpetrator as its main character. The novels Jeg har arvet en mørk skog (2012) by Morten Borgersen and Stormen. En berättelse (2016) by Steve Sem-Sandberg deal with wartime events seen from a present-day I-narrator’s point of view. Both novels incorporate mythology and perverse sexuality, and they ask provocative questions about the causes of wartime violence.
Keywords: guilt; violence and sexuality in Nordic war novels; perpetrator fiction; Morten Borgersen; Steve Sem-Sandberg